Social Mapping of Freshwater Fish Cultivating Communities with Floating Net Cages in Cibinong Village, Jatiluhur District, Purwakarta Regency - Zur'aida, Naurah Nazhifah; Suryana, Asep Agus Handaka; Nurhayati, Atikah; Maulina, Ine (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
This research was carried out in zone 1 or at the same time in Cibinong Village, namely at the Tanggul Usman LLASDP Port. This research began in January 2023 until February 2023. The purpose of this research was to analyze the socio-economic conditions of the KJA cultivating community and the factors that affect the performance of the freshwater fish KJA cultivator business in Cibinong Village, Jatiluhur District, Purwakarta Regency. The method used is descriptive qualitative with a total of 30 KJA cultivators as respondents. Based on the results of the research, it is known that the cultivation pattern developed by the KJA business owners in Cibinong Village is the first pattern of cultivating tilapia with catfish and the second pattern is only gold fish which are cultivated in drawstring nets 2. The first net measuring 7 x 7 m is filled with goldfish, the second net is a kolor 2 measuring 7 x 14 m filled with tilapia, and the bottom net is kolor 4 measuring 14 x 14 m filled with catfish. Some of the social and economic factors studied, which have the most influence on the performance of cultivators in the KJA business in Cibinong Village, are owned capital. The fish seeds that were stocked were 40 fish/kg in one cage, 125 kg were stocked in one cage.